2020
DOI: 10.1371/journal.pone.0238093
|View full text |Cite
|
Sign up to set email alerts
|

The influence of hip muscle strength on gait in individuals with a unilateral transfemoral amputation

Abstract: Introduction A unilateral transfemoral amputation (TFA) has a major impact on function. A leg-length discrepancy is the primary structural change, accompanied by the loss of lower-limb muscle volume and function. Prostheses can help individuals with a TFA to regain function, but such individuals still do not reach the functional level of unimpaired peers and exhibit gait deviations. This study gives insight into the causality between residual limb strength and gait deviations in individuals with a TFA. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 45 publications
2
18
0
3
Order By: Relevance
“…During upslope walking, the positive hip work of the residual limb was 68% of the work produced by the hip of AB subjects. This is consistent with force deficit at the hip of transfemoral amputees which has been quantified to about 30% of the maximum isometric force compared to able bodied subjects (Heitzmann et al, 2020). The huge deficit of positive work produced by the prosthetic ankle cannot be compensated by the residual hip which led to a summed ankle-knee-hip work of 0.12 +/-0.07 J/kg on level ground and 0.26 +/-0.14 J/kg during upslope walking.…”
Section: Discussionsupporting
confidence: 87%
“…During upslope walking, the positive hip work of the residual limb was 68% of the work produced by the hip of AB subjects. This is consistent with force deficit at the hip of transfemoral amputees which has been quantified to about 30% of the maximum isometric force compared to able bodied subjects (Heitzmann et al, 2020). The huge deficit of positive work produced by the prosthetic ankle cannot be compensated by the residual hip which led to a summed ankle-knee-hip work of 0.12 +/-0.07 J/kg on level ground and 0.26 +/-0.14 J/kg during upslope walking.…”
Section: Discussionsupporting
confidence: 87%
“…Before BAP implantation, the individuals in the current study demonstrated differences in frontal plane movement patterns from reference values in line with those reported in prior work, including widened step width, increased hip abduction, and increased ipsilateral trunk lean during single limb support on the prosthetic limb [ 17 , 18 ]. This compensatory pattern is thought to aid stability over the prosthetic knee and ankle components [ 28 , 29 ], reduce pressure on the mediolateral aspect of the residual limb within the socket and improve comfort [ 3 , 30 ], stabilize the residual limb against the lateral wall of the socket, and/or decrease muscular work by a weak or mechanically disadvantaged hip abductor [ 31 , 32 ]. Further, an ipsilateral pelvic hike and compensatory decrease in trunk-pelvis angle during prosthetic limb swing was also observed among the current participants pre-implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Transfemoral amputation negatively affects the abductor and adductor muscles of the hip. It also negatively affects flexion and extension of the back and abdominal muscles 39 . There is also a direct relationship between limb length in the amputated area and the generated force moment and isokinetic contraction force.…”
Section: Discussionmentioning
confidence: 99%